2016
DOI: 10.1111/tri.12756
|View full text |Cite
|
Sign up to set email alerts
|

Good outcome after liver transplantation for ALD without a 6 months abstinence rule prior to transplantation including post-transplant CDT monitoring for alcohol relapse assessment - a retrospective study

Abstract: SUMMARYAlcoholic liver disease (ALD) is the second most common indication for liver transplantation (LT). The utility of fixed intervals of abstinence prior to listing is still a matter of discussion. Furthermore, post-LT long-term observation is challenging, and biomarkers as carbohydrate-deficient transferrin (CDT) may help to identify alcohol relapse. We retrospectively analyzed data from patients receiving LT for ALD from 1996 to 2012. A defined period of alcohol abstinence prior to listing was not a preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…It is estimated that approximately 13,000 patients die from alcohol‐related liver disease annually in the United States with increasing deaths among those under the age of 40 years; yet, only ~2000 annually undergo LT for this indication. This suggests that there is a larger pool of patients who may benefit from LT. As the duration of abstinence is deemphasized in favor of broader psychosocial profiling, the characteristics of ALD patients on the waiting list may change and, in turn, influence WL outcomes . Clearly, as the indication for LT among patients with ALD expands, continued evaluation of the WL outcomes will be important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that approximately 13,000 patients die from alcohol‐related liver disease annually in the United States with increasing deaths among those under the age of 40 years; yet, only ~2000 annually undergo LT for this indication. This suggests that there is a larger pool of patients who may benefit from LT. As the duration of abstinence is deemphasized in favor of broader psychosocial profiling, the characteristics of ALD patients on the waiting list may change and, in turn, influence WL outcomes . Clearly, as the indication for LT among patients with ALD expands, continued evaluation of the WL outcomes will be important.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a larger pool of patients who may benefit from LT. As the duration of abstinence is deemphasized in favor of broader psychosocial profiling, the characteristics of ALD patients on the waiting list may change and, in turn, influence WL outcomes. (31,32) Clearly, as the indication for LT among patients with ALD expands, (15) continued evaluation of the WL outcomes will be important. However, one of the potential concerns of expanding criteria for LT in ALD patients is the risk of worsening posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Post‐OLT monitoring of alcohol consumption by alcohol markers has also been found to be an important tool for detection of a relapse , which occurs in 5–21% of patients . In case timely psychological support is not offered, severe graft injury occurs resulting in poor patient survival prognosis .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the results of these investigations have showed the positive results of the “6‐month abstinence rule”, which suggested that patients who did not abstain from alcohol intake for at least 6 months should not be listed for LT, due to their high relapse rate . However, this rule has recently been reconsidered in many centers and some authors have demonstrated that the opinion of an addiction specialist may be crucial for the inclusion of these patients on the waiting list regardless of the period of abstinence …”
Section: Introductionmentioning
confidence: 99%
“…17 However, this rule has recently been reconsidered in many centers and some authors have demonstrated that the opinion of an addiction specialist may be crucial for the inclusion of these patients on the waiting list regardless of the period of abstinence. 18 Few data are available on the procedure and the practice of offering support to the patients before and after LT to prevent alcohol relapse. [19][20][21] It is widely agreed that patients with alcohol use disorders being considered for LT should undergo evaluation by a professional staff involved in rehabilitation for alcohol abuse and dependence, but there are no definite rules for planning an effective support involving family and caregivers.…”
mentioning
confidence: 99%